A double blind, placebo controlled trial of intravenous methylprednisolone in systemic lupus erythematosus. - Mackworth-Young, C G (1988)
A double blind, placebo controlled trial was performed in 25 patients to study the use of intravenous methylprednisolone (IVMP) in the treatment of active systemic lupus erythematosus (SLE). The trial examined the additive effect of IVMP on a background of conventional oral steroid treatment. Patients were followed up for six months. The results showed a trend towards more consistent overall improvement in the first two weeks after IVMP administration compared with placebo, but this difference was not maintained at one month or subsequently. They also suggested a quicker resolution of hypocomplementaemia in the treatment group. Other parameters of disease activity showed no difference. Side effects were generally mild and were similar in incidence between the two groups. Thus it is concluded that IVMP may improve initial suppression of active lupus in some patients when added to conventional oral steroid treatment, but that this additional benefit is not maintained; IVMP is, however, a relatively safe treatment when used in this way.